Analysis of Arabic Language Learning Strategies Based on Learner Characteristics in Madrasah Aliyah: a Descriptive Qualitative Study - Sanniya Tus Salwa; Silva Fazriatus Sopiah; Wildan Firdaus (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to identify the characteristics of Madrasah Aliyah students as the foundation for designing effective Arabic language learning strategies. In addition, the study analyzes the strategies employed by teachers, describes their implementation in classroom activities, and reveals the supporting and inhibiting factors. The findings are expected to contribute to the development of more adaptive Arabic language instruction that aligns with learners’ needs. This research employs a descriptive qualitative approach to gain an in-depth understanding of the implementation of Arabic language learning strategies based on learner characteristics in Madrasah Aliyah. Data were collected through observation, interviews, and documentation, with primary data obtained from teachers, students, and instructional documents, and secondary data from syllabi, lesson plans, and relevant literature. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, resulting in comprehensive and credible findings. The results indicate that Madrasah Aliyah students possess diverse prior knowledge, learning styles, and levels of motivation, requiring teachers to adjust their Arabic language learning strategies accordingly. Teachers employed communicative approaches, differentiated instruction, project-based learning, the grammar–translation method, and technology-supported learning. Strategy implementation was carried out through assessment-based planning, interactive teaching, and varied evaluation techniques. Supporting factors included teacher competence and adequate facilities, while challenges emerged from heterogeneous student abilities, low motivation, and limited instructional time.